The acceptability, feasibility, and usability of a virtual reality pain education and rehabilitation program for Veterans: a mixed-methods study - Mardon, Amelia K.; Wilson, Dianne; Leake, Hayley B.; Harvie, Daniel; Andrade, Andre; Chalmers, K. Jane; Bowes, Aaron; Moseley, G. Lorimer (Frontiers in Pain Research, 2025)
IntroductionPersistent pain is a leading cause of medical discharges for Veterans. Pain science education (PSE) aims to better people's understanding about pain and is effective at reducing pain and depressive symptoms in Veterans. Preliminary evidence suggests virtual reality (VR)-delivered PSE has clinical benefits for people with persistent pain. This study investigated the acceptability, feasibility, and usability for VR-PSE for Veterans with persistent pain.MethodsVeterans (n = 7) and healthcare professionals (HCPs) experienced in treating Veterans (n = 5) participated in workshops that involved working through the VR-PSE program, online questionnaires, and a focus group. Quantitative data were analysed by descriptive statistics. Qualitative data were analysed using a framework analysis according to the Theoretical Framework of Acceptability (TFA). A mixed-methods analysis combined the quantitative and qualitative data via triangulation, with the findings presented according to the TFA domains.ResultsThe VR-PSE program was considered easy to use, engaging, and adaptable for different functional capabilities. Appropriate screening for contraindications prior to using the VR-PSE program was considered important by HCPs. Both Veterans and HCPs emphasized the need for a trusting client-clinician relationship to improve the acceptability of the VR-PSE program.DiscussionOverall, the VR-PSE program was found to be acceptable, feasible, and usable and may be a useful tool to incorporate into the clinical management of Veterans with persistent pain. Further research is needed to investigate the efficacy of VR-PSE programs on clinical outcomes for Veterans with persistent pain.